Assessment of complications of transurethral resection of the prostate using Clavien-Dindo classification in South Eastern Nigeria - Timothy Uzoma Mbaeri; Joseph Amauzo Abiahu; Emmanuel Ahuizechukwu Obiesie; Chinonso Odo; Kingsley Chidi Oranusi; Alexander Maduaburochukwu Ekwunife Nwofor; Jideofor Chukwuma Orakwe (Nigerian Journal of Surgery, 2020)
Background: Benign prostatic hyperplasia is one of the most common diseases in aging males. For men that need surgical treatment, transurethral resection of the prostate (TURP) is the gold standard. The aim of this article is to retrospectively review the complications of TURP over a 3-year period in Nnamdi Azikiwe University Teaching Hospital Nnewi and a Specialist Urology Center in Awka all in Anambra South-East Nigeria using Clavien-Dindo classification. Patients and Methods: The study was a retrospective review of consecutive TURPs done over a 3-year period. Patients' information and complications arising from the procedure were collected and graded using the Clavien-Dindo classification with a pro forma designed for the study and analyzed with the Statistical Package for the Social Sciences software version 20.0. Results: Ninety-seven patients had TURP during the period of this study. Twenty-nine complications were noted in 24 patients. The postoperative morbidity rate was 24.74%, and no mortality was recorded. Most of the complications were grade 2 (55%), followed by grade 1 and 3 (20.69%) each. Grade 4a complication accounted for only 3.45%. No grade 5 complication was recorded. Conclusion: TURP is safe, with minimal life-threatening morbidity even in a resource-poor economy where TURP is gradually gaining grounds.